Pathomorphological changes in the lung tissues of Syrian hamsters during experimental infection with SARS‐COV‐2 - L. V. Shestopalova; W. Lee; A. Yu. Filippova; M. S. Fedotova; Yu. V. Kononova; M. A. Gulyaeva (Юг России: экология, развитие)
The new coronavirus infection caused by SARS‐CoV‐2 is a dangerous respiratory disease. The aim of the investigation was to study the pathomorphological changes in lungs of Syrian hamsters infected with SARS‐CoV‐2 as is necessary for adequate therapy and prevention of the disease.Syrian hamsters of the SPF category were infected intranasally with a dose of 5×105TCID50 SARS‐CoV‐2/human/RUS/Nsk‐FRCFTM‐1/2020). Animals were euthanised on days 3, 6, 10, 14 and 21 after infection and the lungs were collected. To determine virus replication real‐time RT‐PCR was used. The lungs was used for histological examination. Statistics was performed using Statistics for Windows 10 software.Specific pathological lesions characterising the inflammatory process were detected in all groups of animals. The severity of pathological changes and the volume of lung tissue lesions varied depending on the stage of the disease. The most severe lesions were observed on days 6–10. By day 21, the process of organ structure restoration was noticed.The study showed that pathological changes in the Syrian hamster’s lungs caused by experimental infection with the SARS‐CoV‐2 were multifaceted and complex. In mild cases, congestion and infiltration are observed, and in severe cases, atelectasis and pulmonary edema were life‐threatening. The most severe lesions in lungs were noted on days 6–10. By day 21, the process of restoration was observed.